ENGAGEMENT ANALYSIS OF CRIME NEWS IN THE JAKARTA POST AND THE JAKARTA GLOBE: A SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Novita, Dien (English Education Department of STKIP Pasundan, 2019)
This research explores the application of Appraisal Theory, more specifically, its sub-system Engagement. There were six texts of the Crime News taken from The Jakarta Post and The Jakarta Globe and they were classified into the same topics. The present research aims at comparing the engagement of crime news in The Jakarta Post and The Jakarta Globe employed by appraisal theory. Through this research, the researcher wants to know whether The Jakarta Post and The Jakarta Globe describe the Crime News in Subjective or Objective. It applies quantitative and qualitative methods. The technique used in this research was the total sampling technique since all the data that contains appraising items become the data of this research.